Echocardiographic assessment of patent ductus arteriosus in very low birthweight infants over time: prospective observational study. (17th January 2018) - Yum, Sook Kyung; Moon, Cheong-Jun; Youn, Young-Ah; Lee, Jae Young; Sung, In Kyung
Abstract: Background: We aimed to determine the echocardiographic parameters that can predict the presence of patent ductus arteriosus (PDA) and haemodynamically significant ductus arteriosus (HSDA) at different time points. Methods: Echocardiogram was performed on postnatal days 3 and 7(D3-Echo and D7-Echo, respectively) in 71 very low birthweight infants with a median gestational age of 28.0 weeks. We first assessed the correlation between D3-Echo findings among infants with ductal patency and persistent ductal patency on D7-Echo. We subsequently assessed the correlation between D7-Echo findings and ultimate need for PDA treatment. Results: Forty-nine (69.0%) infants had ductal patency on D3-Echo, and 32(65.3%) of these had persistent PDA on D7-Echo. Twenty of the latter (62.5%) underwent PDA treatment at a median chronological age of 19 days. PDA treatment was significantly correlated with DA size and DA peak-systolic-to-end-diastolic velocity(S/D) ratio on D3- and D7-Echo. Receiver operating characteristic curve analysis revealed that DA size ≥2.040 mm and S/D ratio ≥2.016 had fair sensitivity, specificity, and predictive values for PDA treatment. Conclusion: The significance of different echocardiographic parameters associated with future ductal patency or HSDA depends on the time of assessment. DA size and S/D ratio on day 7 are two reliable indicators of the need for future PDA treatment.